Challenges for weed management in African rice systems in a changing climate - Rodenburg, J.; Meinke, Holger; Johnson, D.E. (Cambridge University Press, 2011)
Global changes including increases in temperature, atmospheric greenhouse gases, soil degradation and competition for land and water resources, will have multiple impacts on rice production systems in Africa. These changes will affect weed communities, and management approaches must be adapted to take this into account. Higher temperatures and limited water availability will generally advantage C4 over C3 plants (e.g. rice). Conversely, elevated carbon dioxide (CO2) levels will improve the competitiveness of rice relative to C4 weeds, which comprise many of the problem weeds of rice. Increased atmospheric CO2 levels may also improve tolerance of rice against parasitic weeds, while prevalence of parasitic species may be amplified by soil degradation and more frequent droughts or floods. Elevated CO2 levels tend to promote growth below-ground relative to above-ground, particularly in perennial (C3) species. This may render mechanical control of weeds within a cropping season less effective or even counterproductive. Increased CO2 levels, rainfall and temperature may also reduce the effectiveness of chemical control, while the implementation of adaptation technologies, such as water-saving irrigation regimes, will have negative consequences for rice–weed competition. Rain-fed production systems are prevalent throughout Africa and these are likely to be most vulnerable to direct effects of climate change (e.g. higher temperatures and changes in rainfall patterns). Effective weed management strategies in these environments could encompass off-season tillage, the use of well-adapted cultivars (i.e. those with drought and heat tolerance, high weed competitiveness and parasitic weed resistance or tolerance) and rotations, intercropping or short, off-season fallows with weed-suppressive legumes including those that suppress parasitic weeds. In irrigated, non-flooded rice systems, weeds are expected to become more serious. Specifically, perennial rhizomatous C3 weeds and species adapted to hydromorphic conditions are expected to increase in prevalence. By implementing an integrated weed management strategy primarily targeted at weed prevention, dependency on flood water, herbicides and mechanical control can be lessened. Off-season deep tillage, stale seed bed techniques, use of clean seeds and irrigation water, competitive cultivars, timely transplanting at optimum spacing and judicious fertilizer timings are suitable candidate components for such a strategy. Integrated, novel approaches must be developed to assist farmers in coping with the challenges of weed control in the future.